2008
DOI: 10.32747/2008.7207242.aphis
|View full text |Cite
|
Sign up to set email alerts
|

Pseudorabies (Aujeszky’s Disease) and Its Eradication: A Review of the U.S. Experience

Abstract: This report has been written to serve as a history of the U.S. Aujeszky’s Disease (Pseudorabies) Eradication Program and as a guide when future disease eradication programs are considered. The report provides an overview of the program and its history and is generally nontechnical, with specific sections written by subject matter experts. The information was compiled during 2007, three years after the last four States qualified for Stage V (Free) Status. This eradication effort was formally initiated in 198… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…A similar method was used in the eradication of PRV. In the PRV eradication program, reestablishing negative breeding herd status after PRV infection requires repeated sampling and testing 30 days after the initial test [12]. The underlying mechanism was similar, but the time interval between paired sampling & testing in our practice stems precisely from the latent period of ASFV strain Georgia 2007, the prevalent strain in China [13].…”
Section: Discussionmentioning
confidence: 99%
“…A similar method was used in the eradication of PRV. In the PRV eradication program, reestablishing negative breeding herd status after PRV infection requires repeated sampling and testing 30 days after the initial test [12]. The underlying mechanism was similar, but the time interval between paired sampling & testing in our practice stems precisely from the latent period of ASFV strain Georgia 2007, the prevalent strain in China [13].…”
Section: Discussionmentioning
confidence: 99%
“…First described in 1895 (Kruskal and Mosteller, 1980), statistical sampling was rarely used in livestock surveillance until a synopsis by Cannon and Roe (1982) made the concepts accessible and understandable to field veterinarians. Subsequently, surveillance sample sizes based on binomial sampling distributions were routinely designed into swine disease control programs, for example, the U.S. pseudorabies (Aujeszky's disease) eradication program (Anderson et al, 2008), and became an integral part of the thought processes of swine health specialists.…”
Section: Overviewmentioning
confidence: 99%
“…The need for effective, on-going regional surveillance is obvious, but a workable design is not [12]. Surveillance based on "down-the-road" testing to prove farms free from infection is often performed in government-supported eradication programs, e.g., Aujeszky's disease [13], but is costly and administratively burdensome. Syndromic surveillance [14], i.e., detection based on reports of clinical signs consistent with the pathogen(s) of interest, should meet the need, but Poppensiek and Budd, cited in [15], found that "The greatest single difficulty in a disease-reporting program proved to be the failure of vets to file reports".…”
Section: Introductionmentioning
confidence: 99%